Factors Associated With the Accuracy of Depth Gauge Measurements - Liu, Pengcheng; Xiao, Joanna Xi; Zhao, Chen; Li, Xiaodong; Sun, Guantong; Yang, Fei; Wang, Xiaoqing (Frontiers in Surgery, 2022)
Background: It is important to select appropriate screws in orthopedic surgeries, as excessively long or too short a screw may results failure of the surgeries. This study explored factors that affect the accuracy of measurements in terms of the experience of the surgeons, passage of drilled holes and different depth gauges. Methods: Holes were drilled into fresh porcine femurs with skin in three passages, straight drilling through the metaphysis, straight drilling through the diaphysis, and angled drilling through the diaphysis. Surgeons with different surgical experiences measured the holes with the same depth gauge and using a vernier caliper as gold standard. The length of selected screws, and the time each surgeon spent were recorded. The measurement accuracy was compared based on the experiences of the surgeons and the passage of drilled holes. Further, parameters of depth gauges and 12-mm cortical bone screws from five different manufacturers were measured. Results: A total of 13 surgeons participated in 585 measurements in this study, and each surgeon completed 45 measurements. For the surgeons in the senior, intermediate, and junior groups, the average time spent in measurements was 689 s, 833 s and 785 s with an accuracy of 57.0%, 42.2%, and 31.5%, respectively. The accuracy and measurement efficiency were significantly different among the groups of surgeons (P <0.001). The accuracy of measurements was 45.1% for straight metaphyseal drilling, 43.6% for straight diaphyseal drilling, and 33.3% for angled diaphyseal drilling (P =0.036). Parameters of depth gauges and screws varied among different manufacturers. Conclusion: Both observer factor and objective factors could affect the accuracy of depth gauge measurement. Increased surgeon’s experience was associated with improvements in the accuracy rate and measurement efficiency of drilled holes based on the depth gauge. The accuracy rate varied with hole passages, being the lowest for angled drilled holes.